E-purse option for making small purchases on campus - De La Salle University, Manila (Animo Repository, 2003)
DLSU-Manila offers E-Purse, an electronic/cash-less payment option for making small purchases on campus. The service, which started on August 11 was an optional service for undergraduate and graduate students with smart ID cards. At the moment, only transactions of the Office of the University Registrar are made available.